2016
DOI: 10.1007/s10764-016-9943-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Flexibility as Measured by the Use of Pioneer and Exotic Plants by Two Lemurids: Eulemur collaris and Hapalemur meridionalis

Abstract: Primate responses to habitat alteration vary depending on the species' dietary guild and forest type. Leaves from secondary vegetation can provide nutritious resources to folivorous primates, whereas frugivores, burdened with a scattered spatial and temporal distribution of fruiting resources, require larger home ranges, potentially limiting their ability to cope with altered landscapes. Within coastal southeastern Madagascar, we sought to determine whether two lemur species occupying contrasting ecological ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 102 publications
(124 reference statements)
3
20
0
Order By: Relevance
“…We hypothesize that these adjustments were caused by the degradation of the habitat, but they may also reflect some fine-tuning by the lemurs themselves to cope with an unfamiliar environment during the years that followed the release. Since fragmentation is often associated with the loss of large trees and native vegetation from within a habitat, our study confirms that the availability of predictable food sources and/or exotic species that can provide an easy-to-access, nonseasonal food resource may contribute to the settling of the lemurs during the initial stage of colonization (Eppley et al, 2017;Gould & Gabriel, 2015;Irwin et al, 2010).…”
Section: Use Of Exotic and Pioneer Speciessupporting
confidence: 74%
See 2 more Smart Citations
“…We hypothesize that these adjustments were caused by the degradation of the habitat, but they may also reflect some fine-tuning by the lemurs themselves to cope with an unfamiliar environment during the years that followed the release. Since fragmentation is often associated with the loss of large trees and native vegetation from within a habitat, our study confirms that the availability of predictable food sources and/or exotic species that can provide an easy-to-access, nonseasonal food resource may contribute to the settling of the lemurs during the initial stage of colonization (Eppley et al, 2017;Gould & Gabriel, 2015;Irwin et al, 2010).…”
Section: Use Of Exotic and Pioneer Speciessupporting
confidence: 74%
“…This group of strepsirrhines includes either strictly or mainly arboreal species, which makes them particularly vulnerable to habitat loss and fragmentation in a country where around half of the remaining forest (46%) is <100 m away from its edge (Vieilledent et al, 2018). Over the last two decades, numerous studies have demonstrated the impact of habitat fragmentation on lemur species richness at the landscape level (Dunham, Erhart, Overdorff, & Wright, 2008; Ganzhorn & Eisenbeiß, 2001; Steffens & Lehman, 2018), their behavioral and ecological response within and between fragments (Campera et al, 2014; Donati et al, 2011; Eppley et al, 2017; Gould & Gabriel, 2015; Irwin, 2008; Irwin, Raharison, Raubenheimer, Chapman, & Rothman, 2015; Lehman, Rajaonson, & Day, 2006), and the genetic consequences of habitat fragmentation on their populations (Bertoncini et al, 2017; Quéméré, Amelot, Pierson, Crouau‐Roy, & Chikhi, 2012; Radespiel, Rakotondravony, & Chikhi, 2008; Sgarlata et al, 2018). Despite an overall negative effect of fragmentation on lemur persistence, several species have been shown to tolerate some levels of habitat degradation via shifts in activity patterns and in dietary choices (Donati et al, 2016; Irwin et al, 2010; Sato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to be optimistic about lemur persistence in increasingly fragmented and further isolated landscapes, which may lead to future genetic health bottlenecks (Parga, Sauther, Cuozzo, Jacky, & Lawler, 2012). habitat (Eppley et al, 2015(Eppley et al, , 2016(Eppley et al, , 2017Grassi, 2006 (Mittermeier et al, 2010), which may be partially responsible for this contrast with other bamboo lemur species. The greater bamboo lemur (P. simus) used to be one of the most widespread lemur species (Godfrey, Jungers, Simons, Chatrath, & Rakotosamimanana, 1999), but is now restricted to a handful of sites within the eastern humid forests (Ravaloharimanitra et al, 2011;Wright et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected for frugivores which require larger habitat areas to meet their dietary demands, but it was unexpected for both folivore-frugivores and folivores which typically display a level of ecological flexibility allowing them to cope well within fragmented areas. In general, previous site-specific research has shown folivores to be less vulnerable to habitat disturbance and edge effects (Eppley et al, 2015(Eppley et al, , 2017Ganzhorn, 1995;Lehman, Rajaonson, & Day, 2006), while frugivorous lemurs have been shown to be adversely affected by anthropogenic, degraded habitat (Balko & Underwood, 2005;Herrera et al, 2011;White et al, 1995). As frugivorous lemurs are important seed dispersers, they are essential for the maintenance of forest diversity and play a fundamental role in habitat regeneration (Federman et al, 2016;Ganzhorn, Fietz, Rakotovao, Schwab, & Zinner, 1999;Razafindratsima & Dunham, 2014;Wright et al, 2011).…”
Section: Trait-specific Sensitivity To Fragmentationmentioning
confidence: 99%